NATIVE CHARACTERISTIC OF INDIGENOUS INDONESIAN CULTURE AS REFERENCE IN RE-DESIGNING TOURISM AREA - Wawan Ardiyan Suryawan; Ainiyah Intan Permatasari (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2018)
Mount Bromo has been well known nationally and even internationally has stunning natural beauty and unique culture of its inhabitants. Both of these have proved able to attract many local and foreign tourists to visit, so its impact also could be felt directly on the economy improvement of local communities and also for the state's foreign exchange from the tourism sector. The uniqueness of Tengger culture can be regarded as a national treasure that has been maintained by the Government sustainably. An idea that is proposed as an effort to help its preservation is to adopt the concept of Ubud Culture Village in Bali. It is considered the most suitable to be applied because it will not only absorb tourists, but also maintain the authenticity of local culture, especially the function and architectural form of traditional buildings of the Tengger tribe that must also be preserved.